Misdiagnosis of Reactive Lymphadenopathy Remotely After COVID-19 Vaccination: A Case Report and Literature Review - Yu, Qian; Jiang, Wei; Chen, Ni; Li, Jia; Wang, Xiaohui; Li, Maoping; Wang, Dong; Jiang, Lan (Frontiers in Immunology, 2022)
A misdiagnosed case of reactive lymphadenopathy was presented, which occurred 5 and 4 months after the first and second doses of CoronaVac vaccination, respectively. The detection exceeded the referable time interval of the COVID-19 vaccine reaction. This side effect may cause diagnostic uncertainty in patients seeking medical care after vaccination, and an accurate diagnosis is important. Rational judgment should be made in the context of vaccination information, along with subtle imaging interpretations. Ultrasonography can be a preferred choice of imaging for diagnostic workup and evaluation. Although a confirmed diagnosis of vaccine reactive lymphadenopathy cannot be solely achieved based on imaging, the technique provides useful morphological details that assist in the judgment. We propose that cortical thickness is an important imaging sign that needs to be considered, and its decrease may potentially be an early sign for improvement in suspected reactive lymphadenopathy. We also introduced contrast-enhanced ultrasonography in this event and observed the presence and decrease of the hypoperfusion area. The technique may be able to provide functional features of reactive lymph nodes.